c.1 - United Nations. Dept. of economic affairs (New York, 1950)
Facilities for the deposit of savings should be widespread, easily accessible and varied, to provide for different types of saving and savers. Such facilities may be provided either through governmental or private agencies. Governments, apart from acting as the depositories of savings often through a postal savings bank or agricultural bank system-can also encourage the growth of private facilities by appropriate banking legislation, by provision of liquidity for banks, by laws and practices encouraging the use of cheques and other credit instruments and, in general, by policies of financial stability. More specifically, governments can encourage the growth of banking facilities by such measures as regular use of banking institutions, deposits of government funds, and other measures which in detail must depend on particular circumstances.
Keywords: Economic development